2019
DOI: 10.1111/hepr.13447
|View full text |Cite
|
Sign up to set email alerts
|

Acid suppression therapy and its association with spontaneous bacterial peritonitis incidence: A systemic review and meta‐analysis

Abstract: Aim It is well known that the use of proton pump inhibitor (PPI) is widespread in patients with liver cirrhosis. PPI counteracts H2 receptor inhibitor (H2RA) with its strong acid suppression effect. However, there is always a concern that PPI use may increase spontaneous bacteria peritonitis (SBP) development in cirrhotic patients. We aimed to investigate the association between acid suppression therapy (i.e. PPI or H2RA) and SBP through meta‐analysis. Methods We searched PubMed, Medline, Web of Science, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…Proton pump inhibitors (PPIs) are discussed to induce dysbiosis, small intestinal bacteria overgrowth and SBP. [20][21][22][23] To exclude an influence of PPI on mucus thickness, we split our patient cohort into a PPI-untreated group and a PPI-treated group. PPI treatment had no effect on mucus thickness, neither in control nor in cirrhotic patients (figure 1B).…”
Section: Liver Cirrhosis Is Associated With Changes In the Colonic Mumentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are discussed to induce dysbiosis, small intestinal bacteria overgrowth and SBP. [20][21][22][23] To exclude an influence of PPI on mucus thickness, we split our patient cohort into a PPI-untreated group and a PPI-treated group. PPI treatment had no effect on mucus thickness, neither in control nor in cirrhotic patients (figure 1B).…”
Section: Liver Cirrhosis Is Associated With Changes In the Colonic Mumentioning
confidence: 99%
“…Sucralfate and histamine receptor blockers have been used in cirrhotic patients for stress‐ulcer prevention, 35 and post‐band ligation prophylaxis 36,37 . Several recent multi‐center studies have shown there is no increased risk of peritonitis in patients with cirrhosis that take histamine receptor blockers 38,39 . Given the results of our analysis, we favor the discontinuation of PPIs in all patients with cirrhosis without a clear indication 34 .…”
Section: Discussionmentioning
confidence: 76%
“…36,37 Several recent multi-center studies have shown there is no increased risk of peritonitis in patients with cirrhosis that take histamine receptor blockers. 38,39 Given the results of our analysis, we favor the discontinuation of PPIs in all patients with cirrhosis without a clear indication. 34 Histamine receptor blockers and sucralfate can be considered, though there is a lack of controlled studies to support their safety.…”
Section: Discussionmentioning
confidence: 93%
“…Endoscopic haemostasis with or without therapies directed towards the host microbiota are recommended for people with GIB secondary to hepatic cirrhosis 5 6. Proton pump inhibitor therapy is generally avoided as it does not improve outcomes in humans with hepatic failure and can result in spontaneous bacterial peritonitis and increased risk for enteric infections 7. Rather, vasoactive drugs, which selectively constrict the mesenteric arterioles and reduce portal blood flow and pressure, are preferred when GIB cannot be controlled by interventional procedures alone 5.…”
Section: Introductionmentioning
confidence: 99%
“…5 6 Proton pump inhibitor therapy is generally avoided as it does not improve outcomes in humans with hepatic failure and can result in spontaneous bacterial peritonitis and increased risk for enteric infections. 7 Rather, vasoactive drugs, which selectively constrict the mesenteric arterioles and reduce portal blood flow and pressure, are preferred when GIB cannot be controlled by interventional procedures alone. 5 These interventions can help reduce patient morbidity and mortality, reduce the duration of hospitalisation and avoid the need for major surgical procedures.…”
Section: Introductionmentioning
confidence: 99%